An analysis of motivation strategies used within the small‐group Accelerating Mathematics Performance through Practice Strategies (AMPPS‐SG) program. Issue 4 (11th January 2020) - Begeny, John C.; Codding, Robin S.; Wang, Jiayi; Hida, Rahma M.; Patterson, Sierra L.; Kessler, Sarah; Fields‐Turner, Felicia; Ramos, Kimberly A.
Abstract: More than half of students in the USA perform below a proficient level in math. Although evidence suggests that intervention in elementary school is critical to supporting struggling learners, and there are several research‐supported instructional practices to support students with math difficulties, the existing research is limited with regard to the impact of motivational strategies designed to improve students' math skills. This study examined the effectiveness of specific motivational strategies used in the small‐group Accelerating Mathematics Performance through Practice Strategies (AMPPS‐SG) intervention program. A multiple baseline design was used with three instructional groups of second grade students to compare the relative effectiveness of three different conditions on students' math computation skills. Condition 1 included all of the AMPPS‐SG instructional components. Condition 2 included all instructional procedures as well as goal‐setting, performance feedback, and reinforcement for performance. Condition 3 included all components used in Condition 2, as well as a group‐based reward contingency. Results showed that students' performance during Condition 3 was significantly better than performance during Conditions 1 and 2.